Identify the Factors that Influence Working Adults' Financial Management Behavior - Widi Savitri Andriasari; Peni Safitri (International Forum of Researchers and Lecturers, 2025)
In order to identify the elements that motivate young people to manage their finances, this study will examine a number of connected topics, including financial knowledge, financial attitudes, income, and religiosity. Primary data, which are questionnaires that are processed using SPSS 25, and secondary data that provide support are the sources of the study data. The findings demonstrated that financial knowledge and religiosity had an effect and were significant on financial management behavior, while financial attitudes and income did not affect financial management behavior.